Synthesis, phase formation and characterization of Co4Nb 2O9 powders synthesized by solid-state reaction - N. Chaiyo (2018)
A corundum-type structure of cobalt niobate (Co4Nb 2O9) has been synthesized by a solid-state reaction. The formation of the Co4Nb2O9 phase in the calcined powders was investigated as a function of calcination conditions by differential thermal analysis (DTA) and X-ray diffraction (XRD) techniques. Morphology and particle size have been determined by scanning electron microscopy (SEM). It was found that the minor phases of unreacted Co 3O4 tend to form together with the columbite CoNb 2O6 phase at a low calcination temperature and short dwell time. It seems that the single-phase of Co4Nb2O 9 in a corundum phase can be obtained successfully at the calcination conditions of 900°C for 60 min, with heating/cooling rates of 20°C /min. © 2008 Trans Tech Publications, Switzerland.